Determinación de los gases contaminantes en fuentes fijas en las empresas: embutidos Don Jorge y productos lácteos San Enrique - Valencia Lagla, Jeanina de los Ángeles (2018)
The purpose of this project was to determine the possible atmospheric pollution generated by Don Jorge Sausages and San Enrique Dairy Products Companies in Lacunga Canton. To determinate the polluting gases, constant measurements were made with the TESTO 350 Combustion Gas Analyzer that evaluated O2, CO2, CO, NOx, SO2 gases, according to the environmental regulations established in the TULSMA, Book VI, Annex 3, Table 2, which are governed by the USEPA Protocol (United States Environmental Protection Agency) making three measurements per day obtaining representative values for comparison. The research was conducted during one year, and it was divided into three phases to meet the objectives; In the first phase, a diagnosis of the current situation of the companies was made, in the second phase the monitoring was carried out and finally, with the information collected in the field, the results were compared with the current environmental regulations, evidencing compliance with the regulations established with the levels of polluting gases in the companies monitored;" " corresponding to the following contaminating levels for the Company Embutidos Don Jorge within the surveyed walls corresponds to "N" "O" _"x" is 143,046 mg / Nm^3 and "S" "O" _"2" of 28,424 mg / Nm^3; while the concentration levels of San Enrique Dairy Company correspond to "N" "O" _"x" is 60,282 mg / Nm^3 and "S" "O" _"2" is 15,269 mg / Nm^3.The database obtained from the companies monitored is a contribution to the possible decision making in environmental policies at the business and provincial levels; within these policies, constant monitoring, maintenance, equipment changes, compliance with regulations and strict sanctions must be taken into consideration in order to improve the environmental quality of the air in the city.